Q: What is 12m plus 9n-4-10m plus 6n?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

6n - 4 - 3 = 3n + 10 + 4n -7 = 7n - 6n + 10 -17 = n

6n+3=15 6n+3-3=15-3=12 6n = 12 n=12/6 = 2

6n

Yes.

In the expression 6n+3 the variable or the unknown is n

Related questions

6n + 5n is 11n.

12m + 3n - 6m + 7n6m + 10n

12m + 2n - 3m + 11n = 9m + 13n

5mn + 6n - 14

6n = 12 n = 2

I assume that you mean n = 3 6n + 4 = 6(3) + 4 = 18 + 4 = 22

m2 + 12m + 20 = ( m + 2)(m + 10)

-5=6n+7 -5-7=6n+7-7 -12=6n -12/6=6n/6 -2=n

This question as written can be taken two ways: 9m + 6n - 3m + 7n = 6m + 13n, or (9m + 6n) - (3m + 7n) = 9m + 6n - 3m - 7n = 6m - n

15/6n + 6/6n = 21/6n = 7/2n

6n - 4 - 3 = 3n + 10 + 4n -7 = 7n - 6n + 10 -17 = n

7n + 1 = 6n + 8 7n=6n+7 (minus 1 from each side) n=7 (7n-6n equals n, you are left with n=7)